Psychophysiological factors as predictors of second language writing achievement in a computer-based test - Lee, Shu-Ping; Chang, Shujen Lee; Su, Hui-Kai; Cui, Zhen-Yang; Lee, Shin-Da (Frontiers in Psychology, 2022)
Sleep quality, personality, and cognitive load potentially increase second language writing (SLW) anxiety and subsequently affect SLW achievement. This study investigates the predictions of sleep quality, personality (social inhibition/ negative affectivity), and cognitive load (content/ computer) toward SLW anxiety and achievement in a computer-based test. Participants included 172 voluntary undergraduates majoring in English as foreign language. SLW anxiety in a computer-based test, sleep disturbance, personality and cognitive load were assessed with the SLW Anxiety Inventory, Pittsburg Sleep Quality Index, Type-D Personality, and cognitive load questionnaires. A structural equation modeling approach was applied to examine the interdependence among the observed variables. An adequate-fit SLW anxiety model was built (X2 = 6.37, df = 6, p = .383, NFI = .97, CFI = 1.00, RMSEA = .02; R-squared multiple correlations: SLW anxiety a computer-based test = .19, computer-based SLW achievement = .07). The structural model showed that sleep disturbance (+0.17), social inhibition personality (+0.31), and computer-induced cognitive load (+0.16) were significant predictors of SLW anxiety in a computer-based test. Subsequently, SLW anxiety in a computer-based test (-0.16) and computer-induced cognitive load (-0.16) were significant negative predictors of computer-based SLW achievement.